Implementing the Problem-Based Learning Model Supported by Canva-Based Animated Videos on Fourth-Grade Students’ Learning Outcomes in Plane Geometry Characteristics - Putri Azzahra; Fadila Suciana (Journal of Basic Education Research, 2026)
Purpose of the study: This study aims to examine the effect of implementing the Problem-Based Learning model supported by Canva-based animated videos on fourth-grade students’ learning outcomes in plane geometry. Methodology: This study used a quantitative method with a quasi-experimental design, specifically the nonequivalent control group design. The sample was selected through purposive sampling, consisting of fourth-grade students from State Elementary School 15 Simarasok as the experimental group 27 students and State Elementary School 03 Sungai Angek as the control group 27 students. The research instrument was a multiple-choice objective test. Main Findings: The analysis results showed that the mean score of the experimental group was 72.86, while the control group scored 60.03. The hypothesis test using an independent samples t-test indicated a significance value of 0.006 < 0.05 and a t-value greater than the t-table (2.850 > 2.00665). Therefore, it can be concluded that the Problem-Based Learning model supported by Canva-based animated videos has a significant effect on fourth-grade students’ learning outcomes in plane geometry. Novelty/Originality of this study: The novelty of this study lies in the implementation of the Problem-Based Learning model combined with Canva-based animated videos in teaching plane geometry. This approach promotes contextual, interactive, and visual learning to address the abstract nature of the material, thereby improving students’ engagement, conceptual understanding, and learning outcomes at the elementary school level.